Ethynyl‐Linked Donor‐π‐Acceptor Boron Dipyrromethenes for Panchromatic Dye‐Sensitized Solar Cells. Issue 6 (5th April 2017) - Shi, Wen‐Jing; Kinoshita, Takumi; Ng, Dennis K. P.
Abstract: Two boron dipyrromethene (BODIPY) derivatives were prepared as functional materials for applications in dye‐sensitized solar cells (DSSCs). These compounds consist of a donor‐π‐acceptor skeleton in which an electron donor and an electron acceptor/anchoring group are introduced to the opposite C2 and C6 positions of a BODIPY core via an ethynyl linker (compounds DN1 andDN2 ). The molecular structure of one of the key intermediates (compound 8 ) was determined by x‐ray diffraction analysis. Both compounds exhibited panchromatic absorptions in the UV/Vis region. The results of electrochemical studies revealed that the HOMO and LUMO levels of these compounds were suitable for the construction of DSSCs consisting of a TiO2 electrode and an electrolyte based on an I3 − /I − redox couple. The optimized structures, frontier molecular orbitals, and absorption spectra of both sensitizers were calculated using density functional theory. A DSSC prepared using the benzothiadiazole‐containing analogueDN2 exhibited a photovoltaic conversion efficiency of 3.41 %. Abstract : Two boron dipyrromethene (BODIPY) derivatives were prepared as functional materials for applications in dye‐sensitized solar cells (DSSCs). These compounds consist of a donor‐π‐acceptor skeleton in which an electron donor and an electron acceptor/anchoring group are introduced to the opposite C2 and C6 positions of a BODIPY core via an ethynyl linker (compounds DN1 andDN2 ).